Discussion on bone healing rate and expression of cytokines and growth factors in rat models with simple fracture and brain injury - Chunhua Chen; Di Gan; Chensong Yang; Yang Shen (Journal of King Saud University: Science, 2020)
This research aims to analyze the differences in bone healing rate, cytokines content, and growth factor content in rats with fracture and traumatic brain injury. In this study, rat models of tibial fracture (fracture group) and tibial fracture combined with brain injury (combined group) were first constructed. Callus and brain tissue sections of the two groups of rat models were made, and the pathological changes were analyzed by hematoxylin – eosin staining. Tissue sections were made to compare the differences in callus volume, trabecular width, and trabecular bone ratio between the two groups of rats. Taking normal rats as controls, serum samples were collected from rats in the control group, fracture group, and combined group. The differences of levels in nerve growth factor (NGF), insulin-like growth factor 1 (IGF1), bone morphogenetic protein 7 (BMP7), and transforming growth factor β1 (TGFβ1) in serum of different groups of rats were detected by enzyme-linked immunosorbent assay, and the expression of NGF, IGF 1, BMPR7, and TGFβR1 in rat callus was detected by Western-Blot. It was found that the rate of bone healing in the combined group was faster than that in the fracture group. The bone callus volume, trabecular width, and trabecular proportion of the rats in the combined group were significantly higher than those in the fracture group (P < 0.05). The content of NGF, IGF1, BMP7, and TGFβ1 in the serum of the fracture group and the combined group and the expression of their receptor proteins were significantly higher than that of the control group (P < 0.05), but the content of NGF, IGF1, BMP7, and TGF 1 in the serum and the expression of their receptor proteins of the combined group were significantly higher than that of the fracture group (P < 0.05). Accordingly, tibial fractures combined with brain injury can accelerate bone healing, which may be caused by regulating the expression of NGF, IGF1, BMP7, and TGFβ1 and accelerating the binding of its receptors.